Acute renal insufficiency as presentation form of multiple myeloma. - Sousa, A (1991)
Multiple Myeloma (MM) causes a wide range of serious clinical, alterations, including acute renal failure (ARF) often present and contributing to the global mortality of this neoplasm. ARF usually occurs well after MM is diagnosed. We describe a case of ARF in a 42 years old male patient requiring urgent hemodialysis that subsequently proved to have MM. The singularity of this case lead us to review cases of ARF admitted to the Nephrology Department between 1978 and 1990. We describe 7 patients (4 male) with ARF as presenting form of MM. Their mean +/- SD age was 60.0 +/- 10.6 (range 42-73). ARF with conserved diuresis was the presenting form in 6, 5 has systemic infection, and none was hypertensive. Replacement therapy with hemodialysis was needed in 6 patients and plasmapheresis was performed in 3. 4 patients died while admitted, 2 were discharged on chronic hemodialysis and there was recovery of renal function in 1 patient.